Comparative pollen morphology and viability among endangered species of Butia (Arecaceae) and its implications for species delimitation and conservation. (3rd May 2016) - Mourelle, Dominique; Gaiero, Paola; Speroni, Gabriela; Millán, Carina; Gutiérrez, Lucía; Mazzella, Cristina
Abstract : The present study reports the results of pollen analyses on four species of Butia (Arecaceae), Butia odorata, B. yatay, B. paraguayensis and B. lallemantii. Pollen grains were described using light microscopy (LM) and scanning electron microscopy (SEM), and pollen viability was determined by the fluorochromatic reaction (FCR) test. All species of Butia studied produce monosulcate pollen grains with a tectate perforate exine. Additionally, B. odorata and B. paraguayensis produce two pollen grain types, mono- and also trichotomosulcate, which has been considered a derived state of the character. Regarding pollen grain size and shape, there are significant differences in long and short axis lengths, and their ratio. Despite serious regeneration problems which jeopardise population survival in the short-term future, results showed that pollen viability of all species of Butia analysed was high enough to ensure good pollination. Therefore, pollen viability is not the limiting factor for population continuity. This is the first study dealing both with pollen morphology and assessment of pollen viability with the aim of species delimitation within this genus. Additionally, this is the first study providing new information regarding the status of the current Butia populations of southern South America from a palynological point of view.